Humanis And Responsible Childer Caring Model For Community in Ngijo Vilage, Gunungpati, Sub-District (Journal of Private and Commercial Law, 2020)
According to the report "Global Report 2017: Ending Violence in Childhood", 73.7 percent of Indonesian children aged 1 - 14 years experience physical violence and psychological aggression at home as an effort to discipline (violent discipline). Adhered to and used by parents is a contributor to psychological aggression at home and the ease of becoming victims of violence. The aim of this research is first; explore and map childcare models found in the lives of the residents of Ngijo Village, Gunungpati District; Second; evaluating and presenting a humane and responsible childcare model for the community members of the Ngijo Village, Gunungpati District. The research method used is a qualitative approach and doctrinal legal research to evaluate statutory regulations and non-doctrinal legal research. The results of the study are expected to find childcare models found at the site, in the form of authoritarian, authoritative, permissive and uninvolded models. Next, analyze from the findings of childcare models and offer childcare models according to the needs of the locations.